Employing a developmental research approach in the design and development of an online Arabic vocabulary games learning prototype in IIUM - Sahrir, Muhammad Sabri; Md Ghalib, Mohd. Feham (2009)
The design and development research, first proposed by Brown & Collins in the 1990s is currently accepted among other well-known methods for use in educational research to test theory and validate its practicality. Also known as developmental research, design research, design-based research, formative research and design-cased, it has conceptual underpinning and practical aspects of the ‘what’ and ‘how’ of ‘doing’. This paper describes the design and development of an online Arabic vocabulary games learning prototype by using this method for elementary learners in Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). The effort to produce this learning prototype is an attempt to integrate a game-based learning in an online environment, to provide new learning experience for learners who have been through a traditional Arabic teaching and learning methods, and to collect and analyze their feedbacks and responses as the formative evaluation for the design and development principles. The exploration of the game-based learning prototype potential for use in teaching and learning in real setting by learners and teachers is also among the steps taken to evaluate the practicality of the prototype.